A kind of high temperature and high salt gel with increased weight and its preparation method and application

By adding composite salt weighting agent and organic silane modified polyvinyl alcohol fiber to the sealing gel, the problem of insufficient high-temperature resistance of gel in the prior art is solved, and a high-density and high-temperature stable sealing effect is achieved, which is suitable for deep well or ultra-deep well operations.

CN119529785BActive Publication Date: 2025-04-08CHENGDU XIYOUHUAWEI SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510097695.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-08
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

In the prior art, the sealing gel is insufficient in high temperature environments and its density is difficult to increase, resulting in poor sealing performance and difficult to effectively use in deep well or ultra-deep well operations.

Method used

A weightable high-temperature resistant high-salt gel is adopted, which includes ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer as the matrix, and a composite salt weighting agent, an organosilane modified polyvinyl alcohol fiber, an antioxidant and a synergistic antioxidant are added to improve the density and high-temperature resistance of the gel through specific proportions and preparation methods.

Benefits of technology

The high density and high temperature stability of the gel are achieved, and good sealing performance can be maintained at conditions above 220°C, effectively prevent the loss of formation fluid, and is suitable for deep well or ultra-deep well operations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a weightable high temperature and high salt resistant gel and its preparation method and application, which belongs to the technical field of temporary plugging gel for oil and gas fields. It includes the following raw materials: ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, naphthalene-1,4,5-triol, reinforcing crosslinking agent, composite salt weighting agent, modified polyvinyl alcohol fiber, antioxidant, synergistic antioxidant and water. The preparation method includes the following steps: first dispersing ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer in water, then adding composite salt weighting agent, antioxidant, synergistic antioxidant, modified polyvinyl alcohol fiber, naphthalene-1,4,5-triol and other raw materials thereto and stirring evenly, and then reacting at 35-50°C for 2-4h to obtain. This gel has a high density, excellent high temperature resistance and salt resistance, and is applied to temporary plugging or isolating leaking layers, and its plugging effect is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of temporary plugging gels for oil and gas fields, and in particular relates to a weighted high-temperature and high-salt resistant gel and a preparation method and application thereof. Background Art

[0002] Well leakage is a common problem in the drilling process. It not only increases the cost and time of operation, but also may damage the reservoir structure and affect the subsequent oil and gas production. Traditional plugging methods, such as bridge plugging, high water loss plugging and cement slurry plugging, have problems with insufficient permeability and retention capacity when dealing with fractured formations. They are easily diluted after mixing with formation fluids, resulting in unsatisfactory plugging effects. Therefore, how to make the gel effectively penetrate into the cracks and caves to form a dense plugging layer and effectively prevent the loss of formation fluids has attracted much attention from researchers. In addition, the stability of gel in high temperature environment is a major bottleneck restricting its application, especially in deep wells or ultra-deep wells above 200°C. The temperature resistance of ordinary gel is obviously insufficient, and it is difficult to maintain its plugging performance. Deep high-temperature formations also put forward higher requirements on the density and rheological properties of plugging gel. Insufficient density may cause the gel to float under high pressure, while poor rheological properties will affect its penetration and curing effect in cracks and caves. In order to adapt to these extreme conditions, we need to continuously explore how to improve the high temperature resistance of polymer gels and optimize their physical properties, so as to ensure that the gels can still form a dense plugging layer under extreme conditions and effectively prevent the loss of formation fluids. These efforts are not only expected to solve the problem of well leakage, but also provide more reliable technical support for deep and ultra-deep well drilling operations. Summary of the invention

[0003] In view of the above-mentioned prior art, the present invention discloses a weightable high-temperature and high-salt resistant gel and a preparation method thereof, so as to solve the technical problems in the prior art that the plugging gel has weak high-temperature resistance, cannot increase density and has poor plugging performance.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is to provide a weighted high temperature and high salt resistant gel, which comprises the following raw materials in parts by weight: 60-90 parts of ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, 4-8 parts of naphthalene-1,4,5-triol, 2-6 parts of reinforcing crosslinking agent, 30-140 parts of composite salt weighting agent, 9-15 parts of organosilane modified polyvinyl alcohol fiber, 1-3 parts of antioxidant, 1-3 parts of synergistic antioxidant oxidant and 90-110 parts of water; the antioxidant is tert-butyl hydroxytoluene or tert-butyl hydroxybenzoic acid; the synergistic antioxidant is citric acid, tartaric acid or citric acid; the composite salt weighting agent is HWJZ-1; the preparation method of organosilane modified polyvinyl alcohol fiber comprises the following steps: dissolving γ-isocyanate propyltrimethoxysilane in an anhydrous solvent, then immersing the polyvinyl alcohol fiber in the solution, reacting for 1-2 hours under inert gas protection and 20-35°C to obtain the fiber.

[0005] Based on the above technical solution, the present invention can also be improved as follows.

[0006] Furthermore, the anhydrous solvent is anhydrous methanol, anhydrous ethanol, anhydrous tetrahydrofuran, anhydrous dioxane or anhydrous dimethyl sulfoxide; the molecular weight of the polyvinyl alcohol fiber is 50,000-100,000; and the solid-liquid ratio of γ-isocyanate propyltrimethoxysilane, polyvinyl alcohol fiber and anhydrous solvent is 1g:10-20g:80-100mL.

[0007] Furthermore, the weighted high-temperature and high-salt resistant gel comprises the following raw materials in parts by mass: 68 to 80 parts of ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, 5 to 7 parts of naphthalene-1,4,5-triol, 3 to 5 parts of reinforcing crosslinking agent, 60 to 100 parts of composite salt weighting agent, 11 to 13 parts of organosilane modified polyvinyl alcohol fiber, 1 to 3 parts of antioxidant, 1 to 3 parts of synergistic antioxidant and 95 to 105 parts of water.

[0008] Furthermore, the weightable high temperature and high salt resistant gel comprises the following raw materials in parts by mass: 75 parts of ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of reinforcing crosslinking agent, 80 parts of composite salt weighting agent, 12 parts of organosilane modified polyvinyl alcohol fiber, 2 parts of antioxidant, 2 parts of synergistic antioxidant and 100 parts of water.

[0009] Furthermore, the reinforcing cross-linking agent is ethylene glycol or glycerol.

[0010] The invention also discloses a method for preparing the weighted high temperature resistant and high salt gel, which comprises the following steps:

[0011] S1: uniformly dispersing the ethyl acrylate-vinyl acetate copolymer or the methyl methacrylate-vinyl acetate copolymer in water;

[0012] S2: Add the composite salt weighting agent, antioxidant and synergistic antioxidant to the dispersion in step S1, stir evenly, then add the organosilane-modified polyvinyl alcohol fiber and stir evenly, then add naphthalene-1,4,5-triol and the enhanced crosslinking agent and stir evenly, then stir and react at 35-50° C. for 2-4 hours to obtain the product.

[0013] The invention also discloses that the weightable high-temperature-resistant and high-salt gel is applied to temporarily plugging or isolating a leaking layer, and can effectively prevent the loss of working fluid.

[0014] The present invention has the following beneficial effects:

[0015] 1. By adding a composite salt weighting agent, the gel has a higher density, and the gel density is 1.46~1.80g / cm 3 , has a wider range of applications. It can effectively sink into the formation cracks or caves during well completion and repair to form a dense plugging layer. The weighting effect not only improves the plugging ability of the gel, but also reduces the floating phenomenon of the gel under high pressure environment, thereby ensuring the stability of the plugging effect. In addition, the inorganic salt components such as potassium formate, potassium citrate and potassium silicate in the composite salt help to maintain the high-temperature stability of the gel. Sodium polyacrylate and phosphonocarboxylic acid copolymers as polymer electrolytes can provide additional cross-linking points and stability at high temperatures, enhance the network structure of the gel, and improve the high-temperature resistance of the gel. The addition of xanthan gum and hydroxypropyl methylcellulose can increase the viscosity and elasticity of the gel, and further enhance the salt resistance of the gel.

[0016] 2. The gel prepared by the present invention has high thermal stability and chemical stability, and can maintain a good gel state at a constant temperature of 220°C for 15 days, indicating that it is suitable for deep well or ultra-deep well operations; the gel has a good plugging effect on porous sand beds and fractured cores, and can prevent the loss of drilling fluid or completion fluid.

[0017] 3. In the raw materials of the present invention, ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer is used as the matrix material of the gel, so that the gel has good temperature resistance and salt resistance; naphthalene-1,4,5-triol is used as a cross-linking agent, and its molecular structure contains multiple highly reactive hydroxyl groups, which is easy to form a cross-linking structure, and the interaction between gel molecules is enhanced, which helps to enhance the high temperature resistance and salt resistance of the gel; the organosilane-modified polyvinyl alcohol fiber has a strengthening effect on the three-dimensional network skeleton of the gel system, improves the integrity of the gel structure, and inhibits the dispersion of the gel; the organosilane-modified polyvinyl alcohol fiber can also form hydrogen bonds with the polymer molecular chain, further improving the stability of the gel system structure; when preparing the organosilane-modified polyvinyl alcohol fiber , the reaction conditions are controlled to make the isocyanate group in γ-isocyanatepropyltrimethoxysilane react with the hydroxyl group in the polyvinyl alcohol fiber, thereby obtaining organic silane-modified polyvinyl alcohol fiber. The strength and elastic modulus of the modified fiber are improved, and the stability of the gel is further enhanced; in addition, the trimethylsiloxane group is retained in the organic silane-modified polyvinyl alcohol fiber. When this gel is used for oil and gas well plugging, the siloxane in the gel is hydrolyzed to form a silanol group, which can react with the silanol group on the rock surface to form a strong silicon-oxygen bond (Si-O-Si), thereby improving the adhesion and stability of the gel, thereby further improving the plugging performance of the gel; the addition of antioxidants and synergistic antioxidants can prevent the gel from oxidative degradation in a high temperature environment, thereby further enhancing the antioxidant performance of the gel.

[0018] 4. The gel prepared by the present invention has a wide range of applications. It can be used for temporary plugging and isolation of leaking layers, which can effectively prevent the loss of working fluid; it can also temporarily plug and isolate reservoirs to prevent gas channeling, which is beneficial to well control safety; it can be used alone or in combination with other bridging temporary plugging agents; it can also be used as a pre- and post-isolation fluid for cementing fluid and liquid-liquid replacement slurry, which can prevent pollution and improve construction quality. DETAILED DESCRIPTION

[0019] HWJZ-1 comes from Chengdu Xiyou Huawei Technology Co., Ltd. The company has applied for an invention patent for this product. The name of the invention patent is "An environmentally friendly high-density solid-free weighting agent and preparation method", and the patent number is ZL201510018549.8. HWJZ-1 includes the following components by weight percentage: 0.05% (sodium polyacrylate + phosphonocarboxylic acid copolymer), 0.6% (xanthan gum + hydroxypropyl methylcellulose), 1.5% disodium ethylenediaminetetraacetic acid, 2% sodium gluconate and 96.15% (potassium formate + potassium citrate + potassium silicate).

[0020] The features and performance of the present invention are further described in detail below in conjunction with embodiments.

[0021] Example 1

[0022] A weightable high temperature and high salt resistant gel comprises the following raw materials in parts by mass: 75 parts of ethyl acrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of ethylene glycol, 80 parts of HWJZ-1, 12 parts of organosilane-modified polyvinyl alcohol fiber, 2 parts of tert-butyl hydroxytoluene, 2 parts of citric acid and 100 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials comprises the following steps: dissolving 1g of γ-isocyanate propyl trimethoxy silane in 100mL of anhydrous methanol, then immersing 10g of polyvinyl alcohol fiber with a molecular weight of 50,000 in the γ-isocyanate propyl trimethoxy silane solution, stirring and reacting at 30°C for 1.5h, introducing nitrogen for protection during the reaction, washing the fiber with anhydrous methanol after the reaction, and drying at 60°C for 1h to obtain the organosilane-modified polyvinyl alcohol fiber.

[0023] The preparation method of the high temperature and high salt gel that can be weighted in this embodiment comprises the following steps:

[0024] S1: adding ethyl acrylate-vinyl acetate copolymer into water and stirring evenly to obtain a dispersion;

[0025] S2: Add HWJZ-1, tert-butylhydroxytoluene and citric acid to the dispersion, stir and mix evenly, then add organosilane-modified polyvinyl alcohol fiber and stir evenly, then add naphthalene-1,4,5-triol and ethylene glycol and stir evenly, and then react at 40°C for 3h to obtain.

[0026] Example 2

[0027] A weighted high temperature and high salt resistant gel comprises the following raw materials in parts by mass: 60 parts of methyl methacrylate-vinyl acetate copolymer, 5 parts of naphthalene-1,4,5-triol, 3 parts of propylene glycol, 60 parts of HWJZ-1, 11 parts of organosilane-modified polyvinyl alcohol fiber, 1 part of tert-butyl hydroxybenzoic acid, 3 parts of tartaric acid and 110 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials comprises the following steps: dissolving 1g of γ-isocyanate propyl trimethoxy silane in 80mL of anhydrous tetrahydrofuran, then immersing 15g of polyvinyl alcohol fiber with a molecular weight of 80,000 in the γ-isocyanate propyl trimethoxy silane solution, stirring and reacting at 20°C for 2h, introducing nitrogen for protection during the reaction, washing the fiber with anhydrous methanol after the reaction, and drying at 60°C for 1h to obtain the organosilane-modified polyvinyl alcohol fiber.

[0028] The preparation method of the high temperature and high salt gel that can be weighted in this embodiment comprises the following steps:

[0029] S1: adding methyl methacrylate-vinyl acetate copolymer into water and stirring evenly to obtain a dispersion;

[0030] S2: Add HWJZ-1, tert-butylhydroxybenzoic acid and tartaric acid to the dispersion, stir and mix evenly, then add organosilane-modified polyvinyl alcohol fiber and stir evenly, then add naphthalene-1,4,5-triol and propylene glycol and stir evenly, and then react at 35°C for 4h to obtain.

[0031] Example 3

[0032] A weightable high temperature and high salt resistant gel comprises the following raw materials in parts by mass: 90 parts of methyl methacrylate-vinyl acetate copolymer, 8 parts of naphthalene-1,4,5-triol, 6 parts of ethylene glycol, 30 parts of HWJZ-1, 13 parts of organosilane-modified polyvinyl alcohol fiber, 2 parts of tert-butyl hydroxytoluene, 1 part of citric acid and 105 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials comprises the following steps: dissolving 1g of γ-isocyanate propyl trimethoxy silane in 90mL of anhydrous methanol, then immersing 15g of polyvinyl alcohol fiber with a molecular weight of 50,000 in the γ-isocyanate propyl trimethoxy silane solution, stirring and reacting at 30°C for 1h, introducing nitrogen for protection during the reaction, washing the fiber with anhydrous methanol after the reaction, and drying at 60°C for 1h to obtain the organosilane-modified polyvinyl alcohol fiber.

[0033] The preparation method of the high temperature and high salt gel that can be weighted in this embodiment comprises the following steps:

[0034] S1: adding methyl methacrylate-vinyl acetate copolymer into water and stirring evenly to obtain a dispersion;

[0035] S2: Add HWJZ-1, tert-butylhydroxytoluene and citric acid to the dispersion, stir and mix evenly, then add organosilane-modified polyvinyl alcohol fiber and stir evenly, then add naphthalene-1,4,5-triol and ethylene glycol and stir evenly, and then react at 35°C for 2h to obtain.

[0036] Example 4

[0037] A weightable high temperature and high salt resistant gel comprises the following raw materials in parts by mass: 68 parts of methyl methacrylate-vinyl acetate copolymer, 7 parts of naphthalene-1,4,5-triol, 2 parts of propylene glycol, 140 parts of HWJZ-1, 9 parts of organosilane-modified polyvinyl alcohol fiber, 3 parts of tert-butyl hydroxytoluene, 1 part of citric acid and 95 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials comprises the following steps: dissolving 1g of γ-isocyanate propyl trimethoxy silane in 90mL of anhydrous ethanol, then immersing 20g of polyvinyl alcohol fiber with a molecular weight of 100000 in the γ-isocyanate propyl trimethoxy silane solution, stirring and reacting at 35°C for 1h, introducing nitrogen for protection during the reaction, washing the fiber with anhydrous methanol after the reaction, and drying at 60°C for 1h to obtain the organosilane-modified polyvinyl alcohol fiber.

[0038] The preparation method of the high temperature and high salt gel that can be weighted in this embodiment comprises the following steps:

[0039] S1: adding methyl methacrylate-vinyl acetate copolymer into water and stirring evenly to obtain a dispersion;

[0040] S2: Add HWJZ-1, tert-butyl hydroxytoluene and citric acid to the dispersion, stir and mix evenly, then add organosilane-modified polyvinyl alcohol fiber and stir evenly, then add naphthalene-1,4,5-triol and propylene glycol and stir evenly, and then react at 50°C for 2h to obtain.

[0041] Example 5

[0042] A weightable high temperature and high salt resistant gel comprises the following raw materials in parts by mass: 80 parts of ethyl acrylate-vinyl acetate copolymer, 4 parts of naphthalene-1,4,5-triol, 5 parts of propylene glycol, 100 parts of HWJZ-1, 15 parts of organosilane-modified polyvinyl alcohol fiber, 2 parts of tert-butyl hydroxybenzoic acid, 3 parts of citric acid and 90 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials comprises the following steps: dissolving 1g of γ-isocyanate propyl trimethoxy silane in 100mL of anhydrous ethanol, then immersing 10g of polyvinyl alcohol fiber with a molecular weight of 50,000 in the γ-isocyanate propyl trimethoxy silane solution, stirring and reacting at 30°C for 1.5h, introducing nitrogen for protection during the reaction, washing the fiber with anhydrous methanol after the reaction, and drying at 60°C for 1h to obtain the organosilane-modified polyvinyl alcohol fiber.

[0043] The preparation method of the high temperature and high salt gel that can be weighted in this embodiment comprises the following steps:

[0044] S1: adding ethyl acrylate-vinyl acetate copolymer into water and stirring evenly to obtain a dispersion;

[0045] S2: Add HWJZ-1, tert-butylhydroxybenzoic acid and citric acid to the dispersion, stir and mix evenly, then add organosilane-modified polyvinyl alcohol fiber and stir evenly, then add naphthalene-1,4,5-triol and propylene glycol and stir evenly, and then react at 40°C for 2h to obtain.

[0046] Comparative Example 1

[0047] A gel comprises the following raw materials in parts by mass: 75 parts of ethyl acrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of ethylene glycol, 80 parts of HWJZ-1, 2 parts of tert-butylhydroxytoluene, 2 parts of citric acid and 100 parts of water.

[0048] The gel preparation method is the same as that of Example 1, except that no organosilane-modified polyvinyl alcohol fiber is added in step S2.

[0049] Comparative Example 2

[0050] A gel comprises the following raw materials in parts by mass: 75 parts of ethyl acrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of ethylene glycol, 80 parts of HWJZ-1, 12 parts of organosilane-modified polyvinyl alcohol fiber, 2 parts of tert-butyl hydroxytoluene, 2 parts of citric acid and 100 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials comprises the following steps: dissolving 1g of γ-isocyanate propyltrimethoxysilane in 100mL of methanol, then immersing 10g of polyvinyl alcohol fiber with a molecular weight of 50,000 in the γ-isocyanate propyltrimethoxysilane solution, stirring and reacting at 80°C for 5h, introducing nitrogen for protection during the reaction, washing the fiber with methanol after the reaction, and drying at 60°C for 1h to obtain the organosilane-modified polyvinyl alcohol fiber.

[0051] The method for preparing the gel is the same as in Example 1.

[0052] Comparative Example 3

[0053] A gel comprises the following raw materials in parts by mass: 75 parts of ethyl acrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of ethylene glycol, 80 parts of HWJZ-1, 12 parts of polyvinyl alcohol fiber, 2 parts of tert-butyl hydroxytoluene, 2 parts of citric acid and 100 parts of water.

[0054] The gel preparation method is the same as that in Example 1, except that polyvinyl alcohol fibers are added in step S2.

[0055] Comparative Example 4

[0056] A gel comprises the following raw materials in parts by weight: 75 parts of ethyl acrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of ethylene glycol, 2 parts of HWJZ-1, 12 parts of organosilane-modified polyvinyl alcohol fiber, 2 parts of tert-butyl hydroxytoluene, 2 parts of citric acid and 100 parts of water. The preparation method of the organosilane-modified polyvinyl alcohol fiber in the raw materials is the same as that in Example 1.

[0057] The method for preparing the gel is the same as in Example 1.

[0058] Experimental example

[0059] The performance of the weighted high temperature and high salt resistant gel prepared in the embodiment of the present invention is similar, and the performance of the related products is described through testing.

[0060] 1. Density test

[0061] The density of the gels prepared in Examples 1 to 5 and Comparative Example 4 was measured using a drilling fluid densitometer. The results are shown in Table 1. The mass fraction of HWJZ-1 in the raw material of Comparative Example 4 was 2 parts, the gel density was significantly reduced, and the weighting effect was weakened.

[0062] Table 1

[0063]

[0064] 2. High temperature resistance test

[0065] The gels prepared in Examples 1 to 5 were placed at 220° C. for static isothermal aging for 3 d, 5 d, 7 d, 10 d and 15 d, and then a fluidity test was performed to observe the flow state of the gel after different static isothermal aging times and test its fluidity. The test results are shown in Table 2.

[0066] Table 2 Changes in fluidity of gel at different times of static isothermal temperature at 220℃

[0067]

[0068] The fluidity of the gels prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was first tested at room temperature, and then each gel was placed under static constant temperature aging at 140° C. and 200° C. for 16 hours, and its fluidity was tested after cooling. The experimental results are shown in Table 3.

[0069] Table 3

[0070]

[0071] It can be seen from Table 1 and Table 2 that the gel prepared in the embodiment has excellent high temperature resistance. After aging at 220°C for 3 to 10 days, the fluidity of the gel is maintained between 13 and 16 cm, which is significantly lower than that of the comparative example. In addition, the gel in the embodiment maintains a good gel state and toughness, and has no signs of dehydration or degradation on the surface, indicating that the gel prepared in the present invention can withstand a high temperature of 220°C for a long time and can be used for deep well and ultra-deep well operations. In comparative example 1, there is no organosilane-modified polyvinyl alcohol fiber in the raw materials, which cannot further strengthen the network skeleton of the gel system, and the heat resistance of the gel is significantly weakened. In comparative example 2, when preparing the organosilane-modified polyvinyl alcohol fiber, the gel network skeleton is not further strengthened, and the heat resistance of the gel is significantly weakened. When the isocyanate group reacts with the hydroxyl group in the polyvinyl alcohol fiber, due to the high reaction temperature and long reaction time, most of the silanol groups formed after the hydrolysis of siloxane also react with the hydroxyl group in the polyvinyl alcohol fiber, resulting in the fiber structure being too rigid, the fiber flexibility and elastic modulus being reduced, the strengthening effect on the gel network skeleton being weakened, and the high temperature resistance of the gel being reduced; in Comparative Example 3, the polyvinyl alcohol fiber was not modified, and the gel stability was weak; in Comparative Example 4, the number of composite salt weighting agents was too small, resulting in a decrease in the inorganic salt content, and the network structure of the gel was not as stable as the gel network in the embodiment, resulting in a decrease in high temperature stability.

[0072] 3. Salt resistance test

[0073] The gels prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were immersed in a 5 The samples were placed in saline with a concentration of 100 mg / L and aged at 90°C for 3, 5, 10, 30 and 60 days. The elastic modulus was measured at different time points. The test results are shown in Table 4.

[0074] Table 4

[0075]

[0076] It can be seen from the table that the gel prepared in the embodiment is placed in a salt water environment and still has a high elastic modulus after aging at 90°C, indicating that the gel structure is stable and has good salt resistance. Due to the lack of organosilane-modified polyvinyl alcohol fiber, a component for strengthening the network skeleton, in Comparative Example 1, the gel structure may be more susceptible to the influence of the salt water environment, resulting in decreased stability; in Comparative Example 2, the organosilane-modified polyvinyl alcohol fiber obtained by different preparation methods, the reaction of the silanol group with the hydroxyl group in the polyvinyl alcohol fiber will increase the crosslinking degree of the gel, but will cause the fiber elastic modulus to decrease, weaken the strengthening effect on the gel network skeleton, and lead to decreased salt resistance; in Comparative Example 3, the polyvinyl alcohol fiber is not modified, and the fiber elastic modulus is weak; Comparative Example 4 has too few composite salt weighting agents compared with the embodiment, and the effect of enhancing the gel elasticity by xanthan gum and hydroxypropyl methylcellulose is weakened. In addition, the density of the gel is too low, the structure is not dense enough, the gel elasticity is reduced, and the gel salt resistance is reduced.

[0077] 3. Gel plugging properties

[0078] 3.1. Sand bed plugging evaluation

[0079] The FA type non-permeable drilling fluid loss tester sand bed was used to simulate the porous formation. Gel and drilling fluid were added to the FA type non-permeable drilling fluid loss tester sand bed (quartz sand particle size 20-40 mesh, sand bed depth 130mm), and the gel invasion sand bed depth and drilling fluid sand bed loss were tested under the condition of 0.7MPa*30min. The experimental results are shown in Table 5.

[0080] Water-based drilling fluid formula: tap water + 8% bentonite + 0.5% Na 2 CO 3 , and weighted with barite powder to a density of 1.16 g / cm³.

[0081] Plugging agent formula and injection method:

[0082] Plugging agent 1#: Inject 200mL of water-based drilling fluid for pressurization.

[0083] Plugging agent 2#: First, 300 mL of the gel prepared in Example 1 was injected to perform pressure plugging, and then the excess gel on the upper part was poured out, and then 200 mL of water-based drilling fluid was injected to replace it.

[0084] Table 5 Sand bed plugging evaluation results

[0085]

[0086] The experiment shows that when water-based drilling fluid is injected into the sand bed, the drilling fluid quickly passes through the gaps in the sand bed and leaks out immediately after pressurization, without any plugging effect. In the 2# gel plugging agent experiment, the gel is first injected and pressurized, and part of the gel squeezes into the pores of the sand bed to form a gel plug with a firm structure and sufficient viscoelasticity, forming a plugging layer. After water-based drilling fluid is injected and pressurized above the gel plug, the gel plug has a significant plugging effect on the water-based drilling fluid, and the leakage of drilling fluid is greatly reduced.

[0087] 3.2 Core flow displacement device evaluation

[0088] The core flow displacement device was used to simulate the fractured leakage formation. The mineral composition analysis of the natural core is shown in Table 6.

[0089] Table 6

[0090]

[0091] The core is 7-10 cm long and is cut in half. 5-10 through-bending seams are artificially drawn in the middle of the core to form an artificial fracture with an initial permeability of about 10 mD. The core is pre-saturated with a displacement fluid, and then the gel is injected into the core, and appropriate pressure is applied to make it evenly distributed. Then, the gel prepared in Example 1 and Comparative Examples 1-4 is gradually displaced with displacement pressures of 3 MPa, 5 MPa, 8 MPa, 10 MPa and 12 MPa, respectively. The pressure is maintained for a period of time, and the breakthrough pressure is recorded to observe whether the gel penetrates the core. The results are shown in Table 7.

[0092] Table 7

[0093]

[0094] It can be seen from the table that the pressure bearing capacity of the gel prepared in Example 1 can reach 8 MPa. This is because the trimethylsiloxane group is retained in the organosilane-modified polyvinyl alcohol fiber in the gel, and the siloxane in the gel is hydrolyzed to form a silanol group. There are silanol groups on the surface of the natural core. The silanol groups and silanol groups react to form a strong silicon-oxygen bond (Si-O-Si), which improves the adhesion and stability of the gel and improves the plugging performance of the gel.

[0095] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A high temperature and high salt gel that can be increased in weight, characterized in that: The invention comprises the following raw materials in parts by weight: 60-90 parts of ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, 4-8 parts of naphthalene-1,4,5-triol, 2-6 parts of reinforcing crosslinking agent, 30-140 parts of composite salt weighting agent, 9-15 parts of organosilane modified polyvinyl alcohol fiber, 1-3 parts of antioxidant, 1-3 parts of synergistic antioxidant and 90-110 parts of water; the antioxidant is tert-butyl hydroxytoluene or tert-butyl hydroxybenzoic acid; the synergistic antioxidant is citric acid, tartaric acid or citric acid; the composite salt weighting agent is HWJZ-1; the reinforcing crosslinking agent is ethylene glycol or propylene glycol; the preparation method of the organosilane-modified polyvinyl alcohol fiber comprises the following steps: dissolving γ-isocyanate propyltrimethoxysilane in an anhydrous solvent, then immersing the polyvinyl alcohol fiber in the solution, reacting for 1 to 2 hours under the protection of an inert gas at 20 to 35°C, and obtaining the obtained fiber; the molecular weight of the polyvinyl alcohol fiber is 50,000 to 100,000; the solid-liquid ratio of γ-isocyanate propyltrimethoxysilane, polyvinyl alcohol fiber and anhydrous solvent is 1g:10 to 20g:80 to 100mL.

2. The weightable high temperature and high salt resistant gel according to claim 1, characterized in that: The anhydrous solvent is anhydrous methanol, anhydrous ethanol, anhydrous tetrahydrofuran, anhydrous dioxane or anhydrous dimethyl sulfoxide.

3. The weightable high temperature and high salt resistant gel according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 68-80 parts of ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, 5-7 parts of naphthalene-1,4,5-triol, 3-5 parts of reinforcing crosslinking agent, 60-100 parts of composite salt weighting agent, 11-13 parts of organosilane modified polyvinyl alcohol fiber, 1-3 parts of antioxidant, 1-3 parts of synergistic antioxidant and 95-105 parts of water.

4. The weightable high temperature and high salt resistant gel according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 75 parts of ethyl acrylate-vinyl acetate copolymer or methyl methacrylate-vinyl acetate copolymer, 6 parts of naphthalene-1,4,5-triol, 4 parts of reinforcing crosslinking agent, 80 parts of composite salt weighting agent, 12 parts of organosilane modified polyvinyl alcohol fiber, 2 parts of antioxidant, 2 parts of synergistic antioxidant and 100 parts of water.

5. The method for preparing the weightable high temperature and high salt resistant gel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: uniformly dispersing the ethyl acrylate-vinyl acetate copolymer or the methyl methacrylate-vinyl acetate copolymer in water; S2: Add the composite salt weighting agent, the antioxidant and the synergistic antioxidant to the dispersion in step S1, stir evenly, then add the organosilane-modified polyvinyl alcohol fiber and stir evenly, then add the naphthalene-1,4,5-triol and the reinforcing cross-linking agent and stir evenly, then stir and react at 35-50° C. for 2-4 hours to obtain the product.

6. An application of a weighted high temperature and high salt resistant gel, characterized in that: The weighted high temperature resistant and high salt gel according to any one of claims 1 to 4 is applied to temporarily plug or isolate leaking layers.

Citation Information

Patent Citations

  • Environment-friendly high-density solid-free weighting agent and preparation method

    CN104610937A

  • Method for modifying ultrahigh molecular weight polyethylene fiber by plasma treatment

    CN101532244A

  • Anti-wear self-healing material which is synthesized in situ by surface-modified nano hydroxysilicate and boride and preparation method of anti-wear self-healing material

    CN108424807A